Dynamic Hedge: an evidence for brazilian future contracts - Bitencourt, Wanderci Alves (2011)
The farming sector is changing, growing and occupying a position of prominence in the economy. These transformations start to demand a bigger concern with the management of risks of the activity. In this direction, the contracts traded at BM&F had become efficient instruments in the reduction of the market risk, through an operation called hedge. However, there is still the necessity of improving of the econometrical techniques for the estimation of the optimal hedge ratio, therefore, it is observed in the brazilian literature that the majority of the works doesn’t consider some aspects of the behavior of the series of returns. Thus, the present work seeks to analyze two methods for the calculation of these hedge optimal ratio, the conventional model of regression and the bivariate GARCH BEKK model that considers the conditional correlations of the series. The preliminary analysis of the results indicates that the hedge optimal ratio is not constant through time, suggesting that the use of models that consider the time dependence of the series is more realistic. The methodology is applied to the prices of the beef cattle comodity.